Multi-Scale Computational Models of Intervillous Blood Flow in Fetal Growth Restriction: Implications of Anatomical Changes on Syncytiotrophoblast Shear Stress - Lee, Tet Chuan; Gamage, Teena KJB; Spring, Mary; Ramanlal, Isha; Jackson, Toby; Clark, Alys R; James, Joanna L (Elsevier BV, 2026)
INTRODUCTION: The haemodynamics of maternal blood flow in the intervillous space (IVS) impacts placental exchange efficiency. The resulting shear stress can also affect syncytiotrophoblast function, and in turn placental development. Here, we use anatomically-informed multiscale modelling approaches to predict flow in the IVS and syncytiotrophoblast shear stress in fetal growth restriction (FGR). METHODS: Three-dimensional placentone models were established and parameterised to normal and FGR scenarios. Normal term and FGR placental tissue punches were microCT imaged, segmented, and used in tissue-level computational fluid dynamics simulations to predict syncytiotrophoblast shear stress. Tissue and placentone-level models were combined to predict syncytiotrophoblast shear stress ranges. Mechanosensing protein expression was determined by immunohistochemistry. RESULTS: Placentone-level models demonstrate variation in IVS flow velocity across the placental depth, with higher velocity regions at spiral artery mouths that extended further in FGR. Tissue-level models predicted higher levels of syncytiotrophoblast shear stress in FGR. Combined models predicted a greater proportion of tissue is exposed to higher shear stresses in FGR, with ∼2-fold increase in peak shear stress proximal to spiral artery openings. Including septal veins increased penetration of maternal blood and the proportion of tissue exposed to higher shear. In FGR, the syncytiotrophoblast had greater Dynein-1 and lower Kinesin-2 and TRVP6 expression, but no difference in IFT88, Polycystin-2 or Piezo-1 expression. CONCLUSIONS: In FGR, impaired remodelling of the spiral arteries and changes in villous tissue architecture combine to increase the proportion of placental tissue exposed to higher shear stress. Septal veins and central cavities act synergistically to ensure adequate placental perfusion.
Keywords: Fetal growth restriction; Intervillous space; Mechanosensing; Shear stress; Syncytiotrophoblast; 0601 Biochemistry and Cell Biology; 1103 Clinical Sciences; 1114 Paediatrics and Reproductive Medicine; Obstetrics & Reproductive Medicine; 3101 Biochemistry and cell biology; 3215 Reproductive medicine; 4204 Midwifery